In Vitro Regeneration of Anchote (Coccinia abyssinica (Lam.) Cong) Using “Bulla” (Ensete ventricosum (Welw.), Cheesman) as an Alternative Gelling Agent - Destaye Shibabaw; Zerihun Demrew Yigezu (The Scientific World Journal)
In countries that have food security problems like Ethiopia, anchote (Coccinia abyssinica (Lam.) Cogn) holds promising potentials for food, feed, and industrial uses. Efficient utilization of such crops through in vitro propagation is limited due to constraints associated with growth medium components. The present study was therefore conducted to evaluate the effectiveness of Ensete flour (bulla) as a substitute of agar for micropropagation of anchote using nodal explants. The experiment was conducted using different combinations of bulla and agar as a solidifying agent under completely randomized design (CRD) with factorial arrangement. The earliest and highest shoot initiation was observed when a combination of 75 g/L bulla and 2 g/L agar and 65 g/L bulla and 2.8 g/L agar was used as a solidifying agent, respectively. The highest average shoot number, 8.4 and 6.2, was recorded when 75 g/L bulla and 2 g/L agar and 65 g/L bulla and 2.8 g/L agar were used for micropropagation of red and white accessions, respectively. The maximum leaf counts were registered when the MS medium was supplemented with 75 g/L bulla and 2 g/L agar for red (7.6) and 65 g/L bulla and 2.8 g/L agar for white (7.0) accessions. The number of roots was the highest (12.6 and 12.4) on a growth medium supplemented with 65 g/L bulla and 2.8 g/L agar and 75 g/L bulla and 2 g/L agar for white and red accessions, respectively. The present finding showed that bulla has promising potential to substitute agar in plant tissue growth medium; however, characterization of its starch and identifying the primary active components are required.